The role of village apparatus in drafting the Qanun Gampong (village regulations): A study in Lamtutui Village, Peukan Bada, Aceh Besar District - Teuku Muttaqin Mansur; M Adli Abdullah; Nellyana Roesa; Yunita Yunita; Sulaiman Sulaiman; Lia Sautunnida (Geuthèë Institute, Aceh, 2023)
ABSTRACT Recently, the changes in socio-legal culture in Lamtutui Village, Lamteungoh Village, Peukan Bada District, Aceh Besar District, and Aceh Province, potentially lead to the disruption of public order and peace. Then, it raises the concern of community leaders in maintaining the values of local wisdom that live and become an important part of the community. Perhaps, formulating Qanun as village regulation in written form becomes a solution and is expected as social community control that could be used also for the next generation. However, there is a problem of lack of human resources as the village apparatus does not have enough capability in drafting village regulations. This activity aims to assist the apparatus in drafting village regulations as a written legal form. There are several activities have been done, starting from sharing information about the upcoming activities, identifying the substantive materials that are important to be drafted as Qanun, discussing drafting the Qanun Gampong, and strengthening and finalizing the draft. The result of those activities is the draft Village Regulation (Qanun Gampong) Lamtutui concerning Public Order and Peace. This draft of Qanun Gampong was done in a process of participatory manner, not only by the village apparatus but also by several communities that were directly involved in providing insights and suggestions related to the substantive matters of the drafted qanun. Finally, it is hoped that this process not only could be a good example for the local community in maintaining public order and comfort but also role a model for other villages in drafting a similar Gampong Qanun. Keywords: assist, village regulations, comfort and public order ABSTRAKPerubahan hukum dan sosial kemasyarakatan di Desa Lamtutui, Kemukiman Lamteungoh, Kecamatan Peukan Bada, Kabupaten Aceh Besar, Provinsi Aceh akhir-akhir ini berpotensi menjurus pada terganggunya ketertiban dan ketenteraman masyarakat. Hal ini menimbulkan kekhawatiran dari sejumlah tokoh masyarakat dalam mempertahankan nilai-nilai kearifan lokal dan adat yang hidup dan berkembang dalam masyarakat. Salah satu upaya mengatasi permasalahan tersebut adalah melalui pembentukan Qanun Gampong (peraturan desa) dalam bentuk tertulis. Qanun Gampong ini diharapkan menjadi sosial kontrol yang mengikat warga, serta mudah diwariskan kepada generasi penerus. Namun perangkat desa tidak memiliki sumber daya manusia yang mampu menyusun produk Qanun Gampong tersebut. Pengabdian ini bertujuan mendampingi perangkat desa menyusun peraturan desa sebagai produk hukum tertulis. Tahapan kegiatan yaitu: sosialisasi rencana kegiatan, identifikasi kebutuhan materi peraturan yang akan disusun, penyusunan draf rancangan Qanun Gampong, pembahasan draf rancangan, perbaikan draft dan finalisasi draft rancangan Qanun Gampong. Kegiatan ini menghasilkan rancangan Qanun Gampong Lamtutui tentang Ketertiban dan Ketenteraman Masyarakat. Rancangan ini dihasilkan secara partisipatif perangkat desa dan sejumlah masyarakat terlibat langsung memberikan masukan dan saran terkait dengan muatan isi Qanun Gampong yang disusun. Dengan pengabdian ini diharapkan menjadi pedoman bagi masyarakat dalam menjaga ketertiban dan kententeraman masyarakat, serta dapat menjadi model bagi desa-desa lain dalam menyusun Qanun Gampong yang serupa. Kata kunci: Pendampingan, Peraturan Desa, Ketertiban dan Kententeraman Masyarakat.